DOI: 10.29007/5k32
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the femoral J-Curve in the native knee

Abstract: The J-Curve in the native knee as well as the femoral component’s J-Curve after total knee arthroplasty are known to have a high influence on kinematics. Furthermore, the J-Curve’s shape affects ligament strain and tension and consequently already slight changes may strongly alter knee forces and stability. To optimize current implants’ J-Curve design with regard to the population’s morphology, information about the main sources of contour variation is necessary.In this study, a principal component analysis (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…For the combined analyses, the identified radii of the 3D J-Curve’s mean shape are comparable to those of previous studies on the 2D J-Curve [ 11 , 12 , 15 , 27 ]. Most of the parameter values derived in this study are also comparable to a previous study on the 2D J-Curve by our group [ 16 ]. However, a relevant difference regarding the AP length of the medial J-Curve can be seen.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For the combined analyses, the identified radii of the 3D J-Curve’s mean shape are comparable to those of previous studies on the 2D J-Curve [ 11 , 12 , 15 , 27 ]. Most of the parameter values derived in this study are also comparable to a previous study on the 2D J-Curve by our group [ 16 ]. However, a relevant difference regarding the AP length of the medial J-Curve can be seen.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, for future implant systems it might be valuable not only to consider narrow and standard versions but, e.g., high and low curvature implants as well as versions with different offsets. Taking into account the importance of shape mismatches along the articulating surfaces [ 9 , 30 ] as well as the discrepancy between actual implant designs and patient specific J-Curves [ 16 ], the number of additional sizes needed potentially will be very high. Against this background, we agree to the conclusion of Delport et al, that another way could be to customize the implant design to each patient individually [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we only considered AP and ML measures, while many more parameters such as the femoral J‐curve or the posterior condylar offset are linked to the clinical outcome 5,31 . The patient‐specific J‐Curve, for example, shows large interindividual variations in shape and orientation 32 . In addition, we only considered implant mismatch with regard to the overall AP and ML size, while (in contrast to patient specific implants) mismatch of OTS implants, for example, in terms of overhang or underhang can occur along the whole implant–bone interface contour.…”
Section: Discussionmentioning
confidence: 99%
“…5,31 The patientspecific J-Curve, for example, shows large interindividual variations in shape and orientation. 32 In addition, we only considered implant mismatch with regard to the overall AP and ML size, while (in contrast to patient specific implants) mismatch of OTS implants, for example, in terms of overhang or underhang can occur along the whole implant-bone interface contour. However, a recent study showed relevant relationships between parameters of the ML (AP) plane and overall ML (AP) size.…”
Section: F I G U R Ementioning
confidence: 99%